MENTAL HEALTH PROBLEMS IN INDONESIA: EAST-WEST SOCIODEMOGRAPHIC GAPS AND POLICY IMPLICATIONS - Nurmila Kurnia; Nurnaningsih Herya Ulfah; Sapto Adi; Supriyadi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Background: Mental health problems in Indonesia challenge the achievement of the Sustainable Development Goals (SDGs). These issues are influenced by sociodemographic factors and development disparities between the Western Indonesia Region (WIR) and Eastern Indonesia Region (EIR). Aims: This study aims to map mental health problems and identify differences between WIR and EIR. Methods: A cross-sectional design was applied, without inferential testing used, using secondary data from the 2023 Indonesian Health Survey. The initial sample of 877,531 respondents was reduced to 10,059 based on inclusion and exclusion criteria. Sociodemographic factors included age, gender, education, employment, marital status, and residence. The analysis was conducted using spatial and descriptive methods. Results: The prevalence of mental health problems was 0.15% higher in EIR than in WIR. In WIR, cases clustered among unemployed urban residents, while in EIR among employed rural residents. Overall, mental health problems were most prevalent among adults aged 19–59 years who were female, had basic education, were unemployed, married, and lived in urban areas. Conclusion: Residents with mental health problems in WIR and EIR showed disparities in employment and residence. Context-sensitive employment policies and enhanced community-based mental health programs can support mental well-being. These findings highlight mental health equity gaps, provide evidence for policymakers, and emphasize region-specific interventions. Keywords: geographic information system, health policy, mapping, mental health problems.